Do politicamente correto ao incorretamente polido - Neves, Maria Helena De Moura (2014)
The text argues that a linguistic analysis paired with the appreciation of the context of current social stands is highly legitimate, observing, however, that, in different situations, this so-called investigative-appreciative attitude has been transformed in actions and reactions that might become vulgarized in common place, or might even become disfigured in stupidity. The distortions in the assessment of the discourse of the other are now a widespread, the hunt for what is now conventionalized as the politically incorrect in language is just a sample of such a distortion. In this presentation, a number of cases of such a nature is analyzed against cases in which, inversely, the use of language is markedly polite, but the deviation of conduct is made more evident. The objective is to evaluate both cases via the role of intersubjectivity in the construal of discourse, aiming at verifying its conceptual counterpart, with special attention to evidence on the mutual conceptual engagement between interlocutors.